2021
DOI: 10.3389/fnagi.2021.699836
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Genetic Mutations Associated With Behavioral Variant Frontotemporal Dementia in Chinese Han Patients

Abstract: BackgroundBehavioral variant frontotemporal dementia (bvFTD) is a clinically heterogeneous syndrome with high heredity. However, the frequencies of mutations associated with bvFTD have yet to be determined. The aim of the current study was to investigate the frequency of Chinese Han patients harboring genetic bvFTD variants.MethodsA total of 49 bvFTD patients selected from our frontotemporal lobar degeneration database, including 14 familial cases belonging to eight families and 35 sporadic cases were consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…Genomic DNA was extracted from fresh peripheral blood leukocytes, and whole-exome sequencing (WES) libraries were generated using the Agilent SureSelect Human All Exon V6 Kit (Agilent Technologies, Santa Clara, CA, USA). The detailed procedure has been described in our previous study [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from fresh peripheral blood leukocytes, and whole-exome sequencing (WES) libraries were generated using the Agilent SureSelect Human All Exon V6 Kit (Agilent Technologies, Santa Clara, CA, USA). The detailed procedure has been described in our previous study [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The prepared libraries were sequenced using the HiSeq-2000 platform (Illumina, San Diego, CA, USA). DNA sequencing and genetic analysis were performed as previously described 5 . Repeat primed PCR was performed as previously described to obtain a qualitative estimation of the presence of C9orf72-expanded repeats 28 .…”
Section: Genetic Analysesmentioning
confidence: 99%
“…The chromosome 9 open reading frame 72 (C9orf72) hexanucleotide repeat expansion was first discovered in 2011, which is mainly associated with amyotrophic lateral sclerosis (ALS) and/or frontotemporal dementia (FTD), and is characteristic of involvement in the extramotor neocortex, hippocampus, and lower motor neurons [1][2][3] . Recent studies have also revealed C9ofr72 as a causative gene of frontotemporal dementia with parkinsonism (FTDP) 4,5 . However, the underlying pathogenesis of parkinsonism in FTDP with C9orf72 repeat expansion remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 40% of FTD cases are genetic, with the most common cause being mutations of the microtubule-associated protein tau (MAPT) gene, especially in China. FTD is characterized by extensive tau pathology, and the most prevalent clinical phenotype is the behavioral variant of FTD (bvFTD) [ 2 , 3 ]. Increasing evidence has confirmed the presence of pathophysiological changes during the presymptomatic stage of genetic FTD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%